TINU syndrome – Two Clinical Cases of Tubulo-Interstitial Nephritis and Uveitis - Bento, V (2008)
TINU (Tubulo-Interstitial Nephritis and Uveitis)syndrome is a rare disease of unknown aetiology characterised by the association between interstitial nephritis and uveitis. The authors present the cases of two young children whose symptoms began with anorexia and weight loss, associated with renal failure and proteinuria of tubular origin. One child also presented anaemia, glycosuria without hyperglycaemia and microhaematuria. A few months later both developed uveitis. In both cases the renal biopsy showed changes compatible with interstitial nephritis. As interstitial nephritis and uveitis aetiologies were not identified, TINU syndrome was suggested as a possible diagnosis. In both children there was a complete resolution, with one needing systemic steroids and immunosuppressive treatment. TINU syndrome should always be considered in the differential diagnosis of patients with renal and ophthalmologic changes.